USULAN PERBAIKAN KUALITAS LAYANAN KEBERSIHAN DI UNIKA ATMA JAYA KAMPUS SEMANGGI DENGAN INTEGRASI KANO’S MODEL DAN QFD (Studi kasus : PT. X) - Trifenaus Prabu Hidayat; Andre Sugioko; Adrian Fortuna Setiawan (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Atma Jaya is one of the universities that try to sustain support facilities by keeping it clean and maintained. One of the Eforts is cooperating with PT. X Indonesia. Based on the preliminary survey conducted on twenty-four active college students of Atma Jaya Catholic University Campus Semanggi, about 75% of respondents stated that although the officers had to work every day, still indicated the presence of impurities or trash. If this condition is not corrected, then this will have an adverse impact both Atma Jaya and PT. X Indonesia. Based on these issues, the purpose of this study is to find performance and the proposed improvements to enhance the performance quality of cleaning service PT. X at Atma Jaya Catholic University. The methods used are QFD, Kano, Refined Kano’s Model and TQM approach. Variables used in this research are based on research Mai in 2010. Based on the results of the study, respondents tend to be satisfied with the service PT. X Indonesia at Atma Jaya Catholic University. Proposed improvements are to conduct a review of the contents of the contract related to the number of officers working at Atma Jaya Catholic University.